Oral infectivity through carnivorism in murine model of Trypanosoma cruzi infection - Torres, Víctor; Contreras, Víctor; Gutiérrez, Bessy; San Francisco, Juan; Catalán, Alejandro; Vega, José Luis; Moon, Kyung-Mee; Foster, Leonard J.; de Almeida, Rafael F.; Kalergis, Alexis M.; González, Jorge (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Oral transmission of T. cruzi is probably the most frequent transmission mechanism in wild animals. This observation led to the hypothesis that consuming raw or undercooked meat from animals infected with T. cruzi may be responsible for transmitting the infection. Therefore, the general objective of this study was to investigate host-pathogen interactions between the parasite and gastric mucosa and the role of meat consumption from infected animals in the oral transmission of T. cruzi. Methods Cell infectivity assays were performed on AGS cells in the presence or absence of mucin, and the roles of pepsin and acidic pH were determined. Moreover, groups of five female Balb/c mice were fed with muscle tissue obtained from mice in the acute phase of infection by the clone H510 C8C3hvir of T. cruzi, and the infection of the fed mice was monitored by a parasitemia curve. Similarly, we assessed the infective capacity of T. cruzi trypomastigotes and amastigotes by infecting groups of five mice Balb/c females, which were infected orally using a nasogastric probe, and the infection was monitored by a parasitemia curve. Finally, different trypomastigote and amastigote inoculums were used to determine their infective capacities. Adhesion assays of T. cruzi proteins to AGS stomach cells were performed, and the adhered proteins were detected by western blotting using monoclonal or polyclonal antibodies and by LC-MS/MS and bioinformatics analysis. Results Trypomastigote migration in the presence of mucin was reduced by approximately 30%, whereas in the presence of mucin and pepsin at pH 3.5, only a small proportion of parasites were able to migrate (∼6%). Similarly, the ability of TCTs to infect AGS cells in the presence of mucin is reduced by approximately 20%. In all cases, 60–100% of the animals were fed meat from mice infected in the acute phase or infected with trypomastigotes or amastigotes developed high parasitemia, and 80% died around day 40 post-infection. The adhesion assay showed that cruzipain is a molecule of trypomastigotes and amastigotes that binds to AGS cells. LC-MS/MS and bioinformatics analysis, also confirmed that transialidase, cysteine proteinases, and gp63 may be involved in TCTs attachment or invasion of human stomach cells because they can potentially interact with different proteins in the human stomach mucosa. In addition, several human gastric mucins have cysteine protease cleavage sites. Discussion Then, under our experimental conditions, consuming meat from infected animals in the acute phase allows the T. cruzi infection. Similarly, trypomastigotes and amastigotes could infect mice when administered orally, whereas cysteinyl proteinases and trans-sialidase appear to be relevant molecules in this infective process.